Možno tržišče Luke Koper - Zohil, Josip (Annales. Series historia et sociologia, 1998)
The Port of Koper is doing its best to get well acquainted with its market and to expand it, if possible. This is why we have to initially define the geographical area of research by choosing relatively objective criteria and on their bases make a judgement, whether a certain place is in its market areaor if it belongs to the market area of some other ports. Thus defined areais called port's potential market which, however, is not the same for all kinds of goods. The area of research is divided into zones. Goods always arrive from a certain place or are bound for it. As there are many such places and as some of them are geographically near, we have to arrange them in zones and ...
Keywords: blagovni promet; Luka Koper; market; pomorski promet; Port of Koper; pristanišča; tržišče